Análise da possibilidade de melhoria da resistência mecânica de uma cesta de basquete sem elevar seu custo - Neves, Giovanni Henrique Silva das (Universidade Federal de São Carlos, 2024)
Basketball is becoming very popular in Brazil, which makes people from different social classes to start practising the sport. However, to play basketball, it is needed, despite the ball, a hoop to throw the ball in, and the problem is that the most financially accessible products are fragile and can break easily after some time of playing. In order to democratize the practice of basketball, the developing of good and cheap hoops is extremely important. Therefore, in this project, the loads and stresses caused on the main parts of the rim by the constant impacts of the ballwill be analysed. Thus, it will be studied the viability of replacing materials from the hoop, changing its parts geometry or the way it is assembled in order to improve the mechanical strength of the hoop. The study will begin with the understanding of the basketball shooting dynamics, so it will be possible to calculate the force of the impact. Subsequently, the Finite Element Method will be applied in a model created for this process in order to obtain the mechanical stresses generated in the rim due to the shock. The simulations will be made considering the most common models and materials found on the market, which will then be compared with alternative assemblies. The results found in the simulation will enable a critical analysis of the comparisons, ultimately determining if there is an alternative solution for the assembly of the cheapest hoops that presents more durability while remaining accessible.
Study of improving the mechanical resistance of a basketball hoop without increasing cost
Keywords: Resistência mecânica; Cesta; Aro; Basquete; Fadiga; Fratura; Elementos finitos; Redução de custos; Mechanical resistance; Hoop; Rim; Basketball; Fatigue; Fracture; Finite element; Cost reduction; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS